Temporal Activity Patterns and Foraging Behavior by Social Wasps (Hymenoptera, Polistinae) on Fruits of Mangifera indica L. (Anacardiaceae) - Bruno Corrêa Barbosa; Mariana Frias Paschoalini; Fábio Prezoto (Sociobiology)
This research was done in Juiz de Fora, Minas Gerais, Brazil on february 2012, with objective was to determine which species of social wasps visiting mango fruits, their behaviors displayed  by them while foraging and verify which the species of wasps visitors offer risk of accidents to farmers. The studied area was monitored during February 2012, from 8:00 to 17:00. in a 144 hour effort, and the data collected included the time of activity, diversity, aggressiveness and the general behavior of social wasps around the fruits. There were registered a total of 175 individuals of 12 different species, healthy fruits were damaged during the day, and we registered the abundance and richness peaks throughout the day. This study indicated the needs for special care during the harvest, as aggressive wasps are indeed present and the abundant, resulting in a possible increase of the risk for the workers.